PERBANDINGAN PENERAPAN METODE PERAMALAN GUNA MENGOPTIMALKAN PENJUALAN (STUDI KASUS PADA KONVEKSI ASTAPRINT KABUPATEN MAJALENGKA) - Robi Awaluddin; Resky Fauzi; Dikdik Harjadi (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2021)
Convection Astaprint is a company engaged in the trousers textile industry which operates in Majalengka Regency. So far, Astaprint's convection in determining the sale of its products is only based on a benchmark from past sales data. In order to optimize the number of pants sales at Astaprint convection, a forecasting method is needed that can be used as a benchmark to determine the volume of products the company will sell in the future. There are several forecasting methods used, which are simple moving average, exponential smoothing and linear trend. The results of calculations that have been done using the simple moving average forecasting method, exponential smoothing and linear trend turned out to get the most accurate and accurate forecasting method to be applied by Astaprint convection is the linear trend forecasting method. Linear trend method has the lowest forecast error value compared to other forecasting methods, where the value of forecast error obtained is the mean absolute deviation (MAD) = 763.73, mean square error (MSE) = 963116.6, mean absolute percent error (MAPE) = 14,539%.